Spectral effects of varying texture and composition in two‐component "mudpie" simulations: Insights for asteroid (101955) Bennu. (23rd June 2021) - Sen, Antara; Clark, Beth E.; Cloutis, Edward A.; DellaGiustina, Daniella N.; Hendrix, Amanda R.; Simon, Amy A.; Applin, Daniel M.; Parkinson, Alexis; Turenne, Nathalie; Connell, Stephanie; Ferrone, Salvatore M.; Li, Jian‐Yang; et al.
Abstract: Data returned by the OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer) spacecraft have shown that asteroid (101955) Bennu has a globally low‐albedo surface covered in boulders with diverse texture, color, and albedo properties, and an aqueously altered composition dominated by phyllosilicates. To test whether Bennu's color and albedo diversity could be caused by texture and/or composition variations, we performed a laboratory‐based study using simple two‐component mixtures (called "mudpies") of the phyllosilicate saponite and carbon‐rich opaques. Each mudpie is prepared in four different textures: fine powder, coarse particles, sanded slab, and textured rock. We find that a sanded slab made from 90% saponite and 10% lampblack is a good analog for Bennu, and the color and albedo changes due to texture variations are substantial. At 550 nm, texture changes alone can create up to 36% brightness contrast, and in color measured as a 473 nm/847 nm ratio, texture changes can provide up to 18% color contrast. In comparison, Bennu shows approximately 25% albedo and <1% color contrasts from boulder type to boulder type. These findings suggest that if texture contributes to color on Bennu, the texture variations are typically more subtle than what we simulated in the laboratory. According to our study, the color and albedo properties of different boulder types on Bennu are consistent with different concentrations of carbon‐rich opaques (and possibly consistent with variations in carbonate concentration). The variations within each boulder group are consistent with textural differences.